2020
DOI: 10.1177/2055217320934835
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor function in progressive multiple sclerosis

Abstract: Background A sensitive test reflecting subtle sensorimotor changes throughout disease progression independent of mobility impairment is currently lacking in progressive multiple sclerosis. Objectives We examined non-ambulatory measures of upper and lower extremity sensorimotor function that may reveal differences between relapsing–remitting and progressive forms of multiple sclerosis. Methods Cutaneous sensitivity, proprioception, central motor function and mobility were assessed in 32 relapsing–remitting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Recently, differences in proprioceptive acuity have been reported in PwMS based on clinical course, such that people with primary progressive MS have demonstrated lower vibration sensitivity, poorer elbow matching, and overall reduced position sense across ULs when compared to people with relapsing-remitting MS. 5 Moreover, a small percentage of PwMS (i.e. approximately 20%) demonstrate greater matching errors compared to control participants.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Recently, differences in proprioceptive acuity have been reported in PwMS based on clinical course, such that people with primary progressive MS have demonstrated lower vibration sensitivity, poorer elbow matching, and overall reduced position sense across ULs when compared to people with relapsing-remitting MS. 5 Moreover, a small percentage of PwMS (i.e. approximately 20%) demonstrate greater matching errors compared to control participants.…”
Section: Discussionmentioning
confidence: 91%
“…8/43 participants) performed worse than control participants. Miehm and colleagues 5 further demonstrated that PwMS diagnosed with primary progressive MS had greater matching errors compared to control participants and individuals with relapsing-remitting MS. In general, these studies discuss their findings of poor proprioceptive function in light of MS disease progression, such that they emphasize differences between clinical courses 5 or correlations with such clinical measures as performance on the nine-hole peg test (9-HPT).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple Sclerosis (MS) is a debilitating and chronic autoimmune neurodegenerative disease of the central nervous system (CNS) that exhibits inflammation mediated demyelination [ 1 , 2 ]. MS leads to diverse neurological deficits, progressive loss of sensorimotor function, and clinical disability [ 3 , 4 ]. The etiology underlying MS pathogenesis has been proposed to involve environmental factors, particularly exposure to the Epstein–Barr virus (EBV) and vitamin D insufficiencies as well as ultraviolet light exposure, smoking, and stress.…”
Section: Introductionmentioning
confidence: 99%